2021
DOI: 10.1111/ajt.16613
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of solid organ transplant recipients on medicine-taking: Systematic review of qualitative studies

Abstract: Medicine-taking has a paramount role in minimizing graft loss and maximizing health outcomes in solid organ transplant recipients; however, medication regimens are complex and challenging. [1][2][3] These include immunosuppressants and medications to manage comorbidities such as cardiovascular disease, diabetes, and prevent potentially life-threatening transplant complications such as infections over a lifetime. 1,4 The World Health Organization defines adherence as "the extent to which a person's behaviortaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 154 publications
(878 reference statements)
0
12
1
Order By: Relevance
“…IM non-adherence is one of the main reasons for transplant renal failure (7,31). Medicine taking among transplant recipients is a complex and ubiquitous task with significant impacts on outcomes (32). Among solid organ transplant patients, renal transplant patients had the highest IM non-adherence, ranging from 20 to 70% (6,17,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…IM non-adherence is one of the main reasons for transplant renal failure (7,31). Medicine taking among transplant recipients is a complex and ubiquitous task with significant impacts on outcomes (32). Among solid organ transplant patients, renal transplant patients had the highest IM non-adherence, ranging from 20 to 70% (6,17,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The complex regime of immunosuppressive medications and the need for lifelong treatment make transplant recipients exhausted with the use of immunosuppressive medication. 32 , 33 , 39 This study defined that taking immunosuppressive medication causes a perception of being dependent on medication for life and leads to weariness with taking the medication. Furthermore, the study revealed that liver transplant recipients’ perception of being completely healed after transplantation or losing belief in treatment also negatively affected medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A successful organ transplant is a life-changing event and comes with a new set of challenges for recipients, their caregivers, and health professionals. There is a perpetual fragile balance between physical, emotional, and psychosocial needs and the management of the transplant, medication, activities, and relationships (Davidson et al 2017;Tang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence is a life-threatening behaviour which may lead to a relapse of the chronic condition, graft loss in patients with organ transplants, or at worst, death (Tang et al 2021).…”
Section: Non-adherence In Adolescent Transitionmentioning
confidence: 99%